Hepatic Encephalopathy in a Postpartum Patient with Chronic Hepatitis B: A Case Report - Priska Harsanti Devi; I Ketut Mariadi (MEDICINUS, 2026)
Decompensated liver cirrhosis in the postpartum period is rarely reported, particularly in association with chronic hepatitisvB infection. We presented the case of a 33-year-old woman who developed decreased level of consciousness one day afterdelivery. She had no prior history of chronic illness, although her father had passed away from complications of hepatitisvB. Clinical findings included jaundice, ascites, and hepatic encephalopathy. Laboratory results revealed reactive HBsAg, hypoalbuminemia, elevated liver enzymes, hyponatremia, hypokalemia, and markedly elevated total bilirubin. Abdominalultrasound demonstrated cirrhosis with splenomegaly and ascites. The patient was diagnosed with Child-Turcotte-Pughclass C cirrhosis with grade II ascites, grade II hepatic encephalopathy, chronic hepatitis B, and esophageal varices. She received supportive treatment including lactulose, albumin transfusion, and antiviral therapy with tenofovir, resulting inclinical and biochemical improvement after one month. This case highlighted the importance of early screening for hepatitis B during pregnancy to prevent potentially fatal postpartum hepatic decompensation.